Application of Genetic Algorithms to Vector Optimization of the Automatic Control Systems - Severin, Valeriy Petrovich (Institute of Information Theories and Applications FOI ITHEA, 2009)
Methods for calculation of quality indexes for automatic control systems are presented. For the optimization of quality indexes defined only in a stability domain a vector objective function of varied parameters of the system is proposed. The stepwise principle of successive satisfaction of constraints for the passage into the definition domain of quality indexes is considered, as well as a rational mechanism of its realization in the form of the priority optimization of the vector objective function. For the optimization of the vector objective functions genetic algorithms as vector optimization methods are presented. Their application allows one to steer the optimization process from any initial point of the space of varied parameters into the stability domain of the system and to find the optimum of the quality indexes in this domain. The efficiency of the proposed application of vector genetic algorithms for the quality indexes optimization is confirmed by computational experiments.

Представлены методы вычисления показателей качества для систем автоматического управления. Для оптимизации показателей качества, определенных только в области устойчивости, предлагается векторная целевая функция переменных параметров системы. Рассмотрен пошаговый принцип последовательного удовлетворения ограничений для перехода в область определения показателей качества, а также рациональный механизм его реализации в виде приоритетной оптимизации векторной целевой функции. Для оптимизации векторных целевых функций представлены генетические алгоритмы в виде методов векторной оптимизации. Их применение позволяет управлять процессом оптимизации, перейти из любой начальной точки пространства переменных параметров в область устойчивости системы и найти оптимальный показатель качества в этой области. Эффективность предлагаемого применения векторных генетических алгоритмов для оптимизации показателей качества подтверждается вычислительными экспериментами.
Применение генетических алгоритмов для векторной оптимизации систем автоматического управления
Keywords: genetic algorithms; vector optimization methods; automatic control systems; quality indexes; генетические алгоритмы; методы векторной оптимизации; системы автоматического управления; показатели качества